Linguistic and cultural study of the language of advertising (on the material of the English and Karakalpak languages) (Journal of Universal Science Research, 2023)
Translation of advertising today is singled out as a completely separate area of translator's activity, which requires from a specialist not only an ideal knowledge of the stylistic subtleties and cultural nuances of Karakalpak and English languages, but also a clear understanding of the consumers' psychology.